Waqf Land Registration and Its Implications for Legal Certainty: A Case Study in Jember Regency - Wibisono, Alvanto; Mujiburohman, Dian Aries; Khasanah, Dian Dewi (Marcapada: Jurnal Kebijakan Pertanahan, 2025)
This study analyzes the implementation of the waqf land registration acceleration program in Jember Regency as an effort to increase recognition and legal protection of waqf assets. The method used is descriptive-qualitative by combining primary data from interviews and secondary data. This program is implemented through three main approaches: local acceleration, integration with the 2023 PTSL program, and a cross-sector scheme (Lintor) involving the regional government, Ministry of Religious Affairs, Land Office, and Indonesian Waqf Agency. Of the target of 1,000 plots, only 752 waqf plots and 87 lintor plots were successfully certified. The main obstacles include limited KUA infrastructure, unsystematic rotation of officials, data asynchrony between institutions, and low public legal awareness of the importance of certification. This study concludes that the effectiveness of the program is determined by the simplification of procedures, institutional synergy, and public education through religious institutions. Theoretically, this study expands the study of religious agrarian governance by applying a multi-actor approach and offering a collaborative model that can be replicated in other areas. Capacity building of Nazir and sustainable funding are also recommended to encourage the legalization of waqf land nationally and ensure long-term legal certainty.